Islamic Counseling Perspective on Stigma and Inequality in Health Service Access Among Scavengers in Makassar City - A Nurul Mutmainnah; Muhammad Syukur; Firdaus W Suhaeb (Indonesian Journal of Islamic Counseling, 2026)
Informal waste pickers are key actors in the urban recycling system; however, their access to healthcare remains unequal. This study explores the gap in access to and experiences of healthcare services between waste pickers and waste business owners/managers in Makassar, Indonesia. A comparative qualitative approach was used through in-depth interviews with 15 waste pickers, 10 business owners/managers, and 5 health workers, complemented by observations at the Antang temporary waste disposal site (TPS) and three nearby community health centers (Puskesmas). The findings indicate that inequalities are shaped by the interaction of economic, symbolic, and institutional factors. Waste pickers face unstable daily incomes, indirect costs of seeking treatment, limited administrative and digital literacy, longer waiting times, and the stigma associated with "dirty work," which can deter them from seeking care. In contrast, business owners/managers have stronger economic resources and better administrative capacity, facilitating access to services and more effective utilization of the BPJS Kesehatan (Social Security Agency) system. Despite the implementation of the National Health Insurance (JKN) digital system, many waste pickers lack adequate devices or sufficient information, and therefore continue to rely on manual record-keeping. This study shows that formal universal health insurance does not automatically translate into equitable access for informal workers. The study recommends the development of a hybrid service model (digital and in-person), simplification of administrative procedures, and a service approach that is more sensitive to stigma and waste pickers' working conditions.